2021
DOI: 10.1002/cmdc.202100045
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine, a Key Substructure for Antidepressants: Its Role in Developments and Structure‐Activity Relationships

Abstract: Depression is the single largest contributor to global disability with a huge economic and social burden on the world. There are a number of antidepressant drugs on the market, but treatment‐resistant depression and relapse of depression in a large number of patients have increased problems for clinicians. One peculiarity observed in most of the marketed antidepressants is the presence of a piperazine substructure. Although piperazine is also used in the optimization of other pharmacological agents, it is almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 126 publications
(111 reference statements)
0
31
0
Order By: Relevance
“…The molecular tweezer 1 can be used as a suitable chemodosimeter for the detection of piperazine. PZ possesses important pharmacological properties and is used, together with its salts, as an anthelmintic [55], in industrial gas treatments such as CO 2 capture system [56,57], and also as the precursor for a class of psychogenic drugs [58,59]. Piperazine may cause allergic dermatitis [60], and it has been demonstrated that, although not extremely toxic, it has a low biodegradability [61].…”
Section: Sensing Piperazinementioning
confidence: 99%
“…The molecular tweezer 1 can be used as a suitable chemodosimeter for the detection of piperazine. PZ possesses important pharmacological properties and is used, together with its salts, as an anthelmintic [55], in industrial gas treatments such as CO 2 capture system [56,57], and also as the precursor for a class of psychogenic drugs [58,59]. Piperazine may cause allergic dermatitis [60], and it has been demonstrated that, although not extremely toxic, it has a low biodegradability [61].…”
Section: Sensing Piperazinementioning
confidence: 99%
“…This strategy is highly efficient and low-cost, [18] and it is strongly supported by computational approaches (in silico). [18][19][20] Among approved or still under study [21,22] drug repositioning, the repositioning of remdesivir, [23,24] lopinavir/ritonavir, [25][26][27] chloroquine and hydroxychloroquine [17,[28][29][30] for mild to moderate coronavirus infections stand out. [20,31] Drugs like chloroquine and hydroxychloroquine have been widely featured in clinical trials for the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is highly efficient and low‐cost, [18] and it is strongly supported by computational approaches ( in silico ). [ 18 , 19 , 20 ] Among approved or still under study[ 21 , 22 ] drug repositioning, the repositioning of remdesivir,[ 23 , 24 ] lopinavir/ritonavir,[ 25 , 26 , 27 ] chloroquine and hydroxychloroquine[ 17 , 28 , 29 , 30 ] for mild to moderate coronavirus infections stand out. [ 20 , 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[17] Piperazine is a versatile heterocyclic compound reported as a key structural moiety in many CNS active compounds. [18] In anti-depressants drugs, piperazine nucleus is reported to interact with various amino acid residues of the active site of MAO-A enzyme. The piperazine nucleus can be attached to structurally different scaffolds and a library of compounds can be synthesized for biological screening and lead optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Piperazine is a versatile heterocyclic compound reported as a key structural moiety in many CNS active compounds [18] . In anti‐depressants drugs, piperazine nucleus is reported to interact with various amino acid residues of the active site of MAO‐A enzyme.…”
Section: Introductionmentioning
confidence: 99%